Characterization of contaminant leaching from asphalt pavements: A critical review of measurement methods, reclaimed asphalt pavement, porous asphalt, and waste-modified asphalt mixtures. (1st July 2022) - Azadgoleh, Mehrdad Asadi; Mohammadi, Mohammad Mahdi; Ghodrati, Ali; Sharifi, Seyed Sina; Palizban, Seyed Mohammad Mahdi; Ahmadi, Arman; Vahidi, Ehsan; Ayar, Pooyan
Highlights: Different aspects of contaminant leaching from asphalt pavements were reviewed. Contaminant leaching from stockpiled wastes can be reduced by using them in asphalt mixtures. Leaching measurement performance depends on the homogeneity of the asphalt mixture, seasonal changes, and pavement structure. The source of RAP, stockpiling time, and stockpiling technique affect leachate concentration. PAP containing absorbents trapping contaminants chemically can be known as an efficient leaching management system. Abstract: In recent years, the pavement industry has been seeking sustainable development through recycling reclaimed asphalt pavement and reusing other waste materials as replacements for asphalt mixture constituents. Incorporating waste material into asphalt mixture and the presence of pollutants such as exhaust fumes and gasoline due to vehicle traffic may lead to contaminants leaching from asphalt pavements to underlying soil layers and groundwater aquifers, posing serious risks to ecosystems and the environment. To cast light on contaminant leaching from asphalt pavements, this article presents a comprehensive review of the literature that is divided into four research areas: evaluation of leaching measurement methods, leaching from recycled asphalt materials, leaching characteristics of porous asphalt pavements, and waste-modified asphalt mixtures. Moreover, a critical discussion of bibliometric data, literature content and knowledge gaps in this domain is provided to help highway agencies and environmental scientists address contaminant leaching from asphalt pavements. Finally, some potential research directions are suggested for future research works. Graphical abstract: Image, graphical abstract